P-136 Implementation of electronic prescribing and medicines' administration (ePMA) into a hospice setting. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Oakley, Katherine; Simpson, Lynda; Smart, Deborah; Causton, Karen; Regan, Anne; O'Neill, Sue
Abstract : Background ePMA is used in many UK hospitals, but not in hospices. It can reduce prescribing errors, enable more efficient administration of medicines and free up staff to spend more time with patients (Ahmed, Garfield, Jani, Jheeta et al ., 2016). St Helena introduced SystmOne into clinical practice in 2012 and implemented ePMA into the inpatient unit (IPU) in November 2018. Aims: To reduce drug errors, improve patient safety, strengthen information governance, and enable staff to use their time more efficiently. Methods: A project team of IPU and SystmOne managers, senior pharmacy staff and a consultant was set up and pre-implementation research undertaken, including visits to other healthcare settings. A business plan highlighted training needs and cost implications. Specific formularies were built, mobile 'computers on wheels' (COWs) were ordered, the risk register was updated and training sessions for all clinical and pharmacy staff (group and 1-2-1) were delivered. We initially implemented ePMA incrementally as each new patient was admitted, and provided increased technical support to staff, including at evenings and weekends. Results: We identified that 40% of our recorded drug errors may not occur with ePMA, for example lost drug charts. We remained vigilant for new or unanticipated errors, and dealt with them swiftly. Since implementation, the number of drug errors has fallen by 35% (from 28 to 18). A small increase level 2 errors (Hospice UK, 2017), from 3 to 4 has been noted, none related directly to ePMA. Informal feedback from staff and patients has been positive, e.g. nurses have more ward time, patients do not feel the COWs detract from their interactions with staff. Conclusion: The system is now fully embedded in the inpatient setting. This year we plan to complete an audit, support other interested hospices, carry out staff and patient satisfaction surveys and implement discharge medication functionality.